POTENSI VEGETASI DAN DAYA DUKUNG UNTUK HABITAT GAJAH SUMATERA (Elephas maximus sumatranus) DI AREAL PERKEBUNAN SAWIT DAN HUTAN PRODUKSI KECAMATAN SUNGAI MENANG, KABUPATEN OGAN KOMERING ILIR - Garsetiasih Setiasih; Anita Rianti; Mariana Takandjandji (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Forest land converted into palm oil plantations have caused habitat fragmentation of elephant and land degradation. These lead to land use conflict between human and elephant. The conflict often caused the elephant killed and destructed agricultural land. The study was aimed to estimate potential use and carrying capacity of elephant habitat. Data collection of undergrowth vegetation were analyzed using twelve square plots of 1 x 1m, the distance between the plot of 50 m, tree vegetation of seedlings size 1 x 1 m, saplings 5 x 5 m, and trees 20 x 20 m, the distance between the plot of 200 m and of 1000 m lenght. Vegetation used as elephants feed were observed using purposive sampling and systematically procedure. The analysis showed that biomass of plants producing elephant fodder in Tambang Besi were of Cyperus rotundus (3600.26 kg/ha), Cynodon dactylon (346.74 kg/ha), Melaleuca leucadendron (255.21 kg/ha), and Melastoma malabatricum (156.40 kg/ha). While, the highest biomass in Tebing Penigasan plot is Cyperus rotundus (3575 kg/ha), and in Barak Gajah Plot is Isachne globusa (4013.33 kg/ha). The carrying capacity of elephants habitat of Tambang Besi, Tebing Penigasan, and Barak Gajah plots are 0.78, 0.29, and 0.41 individual/ha/day, respectively.